Kajian Yuridis Penggunaan Keterangan Ahli Dalam Tindak Pidana Memperdagangkan Barang Bermerek Palsu - Dominikus Andhika Prakosa (Sebelas Maret University, 2017)
The aim of this research is to know how to use the expert testimony in case evidentiari hearing of couterfeited branded goods trading. The brand which counterfeited by Tri Harsari are CARDILAX,CANADA,JUSTINU,CARDINAL and this research in to know the coresponding of using the expert testimony on case investigation about couterfeiting of branded goods with article 184 of Penal Procedural Law about evidence. This law research is normative law prescriptive with using a case approach, The data collection technique is by using study literature , using deductive, and qualitatively analysis . Counterfeiting brands are contravene with article 91 on Act no 15 years 2001 about Brands so as to be sentenced for one months and 20 day’s .The investigation cases forgery is using an expert testimony on the process of verification The result of this research is explained that the judge assesment on the power of expert testimony on giving an evidence for strengthen the approvement are very considered by judge and affect the judge confidence on giving his decision. The use of expert testimony in explanation on case investigation about couterfeiting of branded goods are in accordance with the provisions of the article 184 of Penal Procedural Law because the information is an instrument of evidence that outlined in article 184 Penal Procedural Law. Keywords: caption expert , a criminal act , marque false trade